2016
DOI: 10.1200/jco.2015.65.8864
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for the Benefit of Gonadotropin-Releasing Hormone Agonist in Preserving Ovarian Function and Fertility in Lymphoma Survivors Treated With Chemotherapy: Final Long-Term Report of a Prospective Randomized Trial

Abstract: To the best of our knowledge, this is the first long-term analysis confirming that GnRHa is not efficient in preventing chemotherapy-induced POF in young patients with lymphoma and did not influence future pregnancy rate. These results reopen the debate about the drug's benefit in that it should not be recommended as standard for fertility preservation in patients with lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(180 citation statements)
references
References 19 publications
1
173
1
5
Order By: Relevance
“…Five studies involved administration of triptorelin intramuscularly [23][24][25][26]35 , one used intranasal buserelin 27 , five used goserelin [28][29][30][31][32] , one administered diphereline 33 and one used leuprolide acetate 34 . In all included studies GnRHa administration was maintained throughout the chemotherapy treatment.…”
Section: Interventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies involved administration of triptorelin intramuscularly [23][24][25][26]35 , one used intranasal buserelin 27 , five used goserelin [28][29][30][31][32] , one administered diphereline 33 and one used leuprolide acetate 34 . In all included studies GnRHa administration was maintained throughout the chemotherapy treatment.…”
Section: Interventionmentioning
confidence: 99%
“…the rate of persistent amenorrhea) at the end of their follow-up. Four studies reported the frequency of POI, defined by persistent amenorrhea and elevated follicle-stimulating hormone (FSH) levels 28,31,34,35 . The duration of follow-up ranged from 6 months 33 to 7 years 25 .…”
Section: Outcomementioning
confidence: 99%
See 3 more Smart Citations